Hubungan Peranan Guru Pendidikan Agama Kristen Dengan Pertumbuhan Iman Peserta Didik - Abraham Tefbana (JURNAL LUXNOS, 2018)
Abstract: In this article the author is concerned about the relationship between the role of Christian Religious Education teachers and the growth of the faith of students, because Christian Religious Education teachers have special competencies that can be emulated by students. Abstrak: Dalam artikel ini penulis konsen membahas tentang hubungan peranan guru Pendidikan Agama Kristen dengan Pertumbuhan iman peserta didik, karena guru Pendidikan Agama Kristen memiliki kompetensi khusus yang dapat diteladani oleh para peserta didik.